Utilization of Soot and 210 Po-210 Pb Disequilibria to Constrain Particulate Organic Carbon Fluxes in the Northeastern South China Sea - Yang, Weifeng; Zhao, Xiufeng; Guo, Laodong; Huang, Bangqin; Chen, Min; Fang, Ziming; Zhang, Xiao; Qiu, Yusheng (Frontiers in Marine Science, 2021)
Black carbon (BC) is believed to be refractory and thus affects the timescale of organic carbon conversion into CO2 and the magnitude of the sink of CO2. However, the fate of BC in the oceans remains poorly understood. Here, 210Po and 210Pb were measured to examine the export of soot in the northeastern South China Sea (SCS). Concentrations of soot decreased from 0.141 ± 0.021 μmol-C L–1 (mean ± SD) in the mixed layer (0–30 m) to 0.087 μmol-C L–1 at the euphotic base (150 m) due to potential photodegradation within the euphotic zone. In the twilight zone, however, the soot showed an increasing pattern along with the total particulate matter and total particulate organic carbon (POC) contents, corresponding to additions from the shelf/slope sediment resuspension through lateral transport. Using the deficits of 210Po, the export flux of soot from the euphotic zone was calculated to be 0.172 ± 0.016 mmol-C m–2 d–1 and increased with depth. Assuming that the soot is entirely refractory below the euphotic zone, the sediment-derived soot fluxes were estimated based on the increase in soot fluxes relative to the base of the euphotic zone, with values varying from 0.149 ± 0.030 to 0.96 ± 0.10 μmol-C L–1. This indicates that sediment resuspension is an important source of soot to the ocean interior in the SCS. Coupling the sediment-derived soot and 210Po-derived POC fluxes gave rise to a Martin Curve-like flux attenuation of local euphotic zone-derived POC in the twilight zone with b value of 0.70 ± 0.01. These results suggest that soot could be useful for constraining in situ POC fluxes and their transport.